Prospective study of bedside inoculation of blood culture bottles with ascitic fluid versus delayed inoculation for the detection of spontaneous bacterial peritonitis - Iyyanna, Girish; F. V., Manjunath; Ng, Taruni (International Journal of Research in Medical Sciences, 2017)
Background: Spontaneous bacterial peritonitis (SBP) is the most common bacterial infection in cirrhosis, accounting for 10%-30% of all reported bacterial infections in the patients admitted to hospital. Spontaneous bacterial peritonitis (SBP) is the most frequent and life-threatening infection in patients with liver cirrhosis. All forms of cirrhosis have been reported to be complicated by SBP. A delay in the time period between the collection of the ascitic fluid sample, and its inoculation into the blood culture media, has been one of the reasons implicated to account for low-test positivity. There was lack of studies for comparing the bacterial yield between bedside inoculated blood culture bottles with ascitic fluid over delayed inoculation in the detection of SBP. Hence this study is done to compare the bacterial yield between bedside inoculated blood culture bottles with ascitic fluid over delayed inoculation for the detection of SBP. Methods: Cross sectional study. Results: Maximum number of cases of cirrhosis with ascites with SBP was seen in the age group of 31-40years (54.4%) with mean age of study population being 39.66years, more common in males, bed side inoculation yielded more positive culture reports compared to delayed inoculation and E. coli and klebsilla being the common organisms. Conclusions: Difference between 2 culture methods in isolating organism in SBP cases was not statically significant. But, among culture positive cases, this study demonstrates that bedside inoculation of blood culture bottles is superior to delayed laboratory inoculation.